Zoom vs. Google Classroom: Which is likely more effective for supporting students’ learning in mathematics? - Siti Anisa Maesaroh; Leni Marlena (Universitas Islam Negeri (UIN) Mataram, 2021)
[English]: The purpose of this study is to predict the probability of successful mathematics online learning using two platforms; Zoom Meeting and Google Classroom, towards students’ learning outcomes. The sample used was sixty-four grade 11 students. Data was collected through a test on matrix topics and then analyzed using probit regression. The results of the analysis show that the student's probability of success to achieve better learning outcomes using Zoom Meeting is 12.46% higher than Google Classroom. In this case, Zoom Meeting can be used as a virtual face-to-face platform, so that the teaching and learning process can be more communicative and interactive compared to Google Classroom, where its use is limited to the delivery of learning content only. Therefore, online learning using Zoom Meeting in mathematics is more recommended because it has a higher chance of improving students’ learning outcomes. [Bahasa]: Penelitian ini bertujuan memprediksi peluang keberhasilan pembelajaran daring matematika menggunakan platform Zoom Meeting dan Google Classroom terhadap hasil belajar siswa. Sampel yang digunakan sebanyak 64 siswa kelas XI. Pengambilan data dilakukan dengan tes hasil belajar pada materi matriks kemudian dianalisis menggunakan regresi probit. Berdasarkan hasil analisis, diperoleh peluang sukses siswa terhadap hasil belajar menggunakan platform Zoom Meeting 12,46% lebih tinggi dibandingkan dengan Google Classroom. Zoom Meeting merupakan platform yang dapat digunakan sebagai sarana tatap muka maya, sehingga pembelajaran dapat lebih komunikatif dan interaktif dibandingkan dengan Google Classroom yang penggunaannya dibatasi untuk penyampaian konten pembelajaran saja. Dengan demikian, pembelajaran daring menggunakan Zoom Meeting lebih direkomendasikan karena berpeluang lebih tinggi untuk meningkatkan hasil belajar matematika siswa.